A study of corrosion to the carbon steel in the present of carbon dioxide - Diyana, Ghazali (2010)
The study describes on effect of several environmental factors of the corrosion rate in the pipeline. Transmission gas pipeline is an important part of oil and gas industries and the carbon steel is a primary material for construction the pipeline due to its low cost and availability,but it is very susceptible to corrosion in CO2 environments.Carbon dioxide(CO2)corrosion is the major problem in oil and gas industries that causes the pipeline failures. Queous carbon dioxide(carbonic acid)is corrosive and corrodes the carbon steel pipelines and it is influenced by several environmental factors such as pH,temperature,partial pressure of CO2, hydrodynamics, etc.Actually there are many types of corrosion which occur in pipeline but in this study only focused on CO2 corrosion and only two environmental factors which is pH and temperature were investigated.In this study,SOLTEQ Corrosion Study Kits,Model BP01 is used as an apparatus to examine the corrosion rate of metal.ased on the result from the experiment,it was stated that acidic condition recorded the corrosion rate of weight loss was very high.In the temperature test with 3.5% NaCl solution, corrosion rate was high at temperature 1200C.From the research,the corrosion occur in high temperature condition and at low pH environment.As the temperature increase,the corrosion rate also increases due to the dissolution of iron ion and formation of weak carbonic acid.The weak carbonic acid dissociates into carbonate and hydrogen ion,which increase the cathodic reaction on the metal surface.In acidic condition,the available H+ ions makes H+ reduction the dominating cathodic reaction and corrosion rate is found to be sensitive at this low pH.